Nanophotonic Platforms for Enhanced Chiral Sensing - Mohammadi, E.; K. L. Tsakmakidis; Askarpour, A.N.; Dehkhoda, P.; Tavakoli, A.; Altug, H. (ACS Photonics, 2018)
Chirality plays an essential role in life, providing unique functionalities to a wide range of biomolecules, chemicals, and drugs, which makes chiral sensing and analysis critically important. The wider application of chiral sensing continues to be constrained by the involved chiral signals being inherently weak. To remedy this, plasmonic and dielectric nanostructures have recently been shown to offer a viable route for enhancing weak circular dichroism (CD) effects, but most relevant studies have thus far been ad hoc, not guided by a rigorous analytical methodology. Here, we report the first analytical treatment of CD enhancement and extraction from a chiral biolayer placed on top of a nanostructured substrate. We derive closed-form expressions of the CD and its functional dependence on the background-chiroptical response, substrate thickness and chirality, as well as on the optical chirality and intensity enhancement provided by the structure. Our results provide key insights into the trade-offs that are to be accommodated in the design and conception of optimal nanophotonic structures for enhancing CD effects for chiral molecule detection. Based on our analysis, we also introduce a practical, dielectric platform for chiral sensing featuring large CD enhancements while exhibiting vanishing chiroptical background noise. © 2018 American Chemical Society.